Association of age and gender distribution of patient undergoing class ii inlay - MALAY, KAUSALYAH KRISNA; SELVAM, DEEPAK; VADIVEL, JAYANTH KUMAR (The journal of contemporary issues in business and government, 2021)
Inlay restorations are one of the intracoronal restorations which is used commonly in dentistry in this era. Inlay restorations are known to be highly retentive compared to composite restorations in restorative procedures. This study was aimed to evaluate the gender prevalence and age distribution among patients undergoing class II inlay restorations who visited saveetha dental college in Chennai. From the record of 86000 cases (June 2019 - April 2020), all cases of class II inlay restorations were used for data analysis. A total of 40 case sheets were retrieved and cross checked for patients age and gender. The collected data was analysed through SPSS 2.0. Pearson correlation test was used for age and gender distribution for patients undergoing class II inlay restoration and Chi square test was done to evaluate the significance between the variables. Results were recorded. The highest age distribution was seen in 34-41 years old (frequency 35.5%) lowest age range for underwent class II inlay restoration was 58-65 years old (frequency 2.5%). The gender distribution showed predominantly male with a frequency of 67.5% (27 patients out of 40 in total), whereas female patients were only 32.5% who had undergone this treatment.Within the limitation of present study, it is concluded that in Saveetha Dental College, statistically no significant difference was seen in age and gender of the patients undergoing class II inlay restoration.